Cofilin: A Promising Protein Implicated in Cancer Metastasis and Apoptosis - Xu, Jing; Huang, Yan; Zhao, Jimeng; Wu, Luyi; Qi, Qin; Liu, Yanan; Li, Guona; Li, Jing; Liu, Huirong; Wu, Huangan (Frontiers in Cell and Developmental Biology, 2021)
Cofilin is an actin-binding protein that regulates filament dynamics and depolymerysion. The over-expression of cofilin is observed in various cancers, cofilin promotes cancer metastasis by regulating cytoskeletal reorganization, lamellipodium formation and epithelial-to-mesenchymal transition. Clinical treatment of cancer regarding cofilin has been explored in aspects of tumour cells apoptosis and cofilin related miRNAs. This review addresses the structure and phosphorylation of cofilin and describes recent findings regarding the function of cofilin in regulating cancer metastasis and apoptosis in tumour cells.